2017
DOI: 10.1111/idh.12269
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to dental care, Sweden 2003‐2013, and clinical correlates of oral health‐related quality of life in 2013

Abstract: Attitudes important in maintaining and improving good oral health, such as preventive care and regular recalls to dentistry, became less important during this period of 10 years. Oral impact was found to be associated with irregular dental visits and limited economy for dental care, individuals with less than 20 remaining teeth, TMD and manifest caries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…The same situation is also found on a research conducted by Meymand in Iran which the average score obtained shows that 80% of the respondents felt satisfied with the quality provided by the hospital. Most of the questions in the research questionnaire ask about the service obtained, the response towards the patients' needs, providing information, explanation about the existing problems, and effective communication (Marine et al, 2014;Edman et al, 2017;Bahari & Azizan, 2013;Meymand et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The same situation is also found on a research conducted by Meymand in Iran which the average score obtained shows that 80% of the respondents felt satisfied with the quality provided by the hospital. Most of the questions in the research questionnaire ask about the service obtained, the response towards the patients' needs, providing information, explanation about the existing problems, and effective communication (Marine et al, 2014;Edman et al, 2017;Bahari & Azizan, 2013;Meymand et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] Population-based studies have shown that prevalence of oral impacts on the quality of life of older people ranged between 14% and 57.8% worldwide. 8,12,14,16 Other less representative cross-sectional studies have found prevalence of OIDP ranging between 57.9% and 92.7%. 7,9,13,15 Of these studies, few considered the impact of characteristics other than clinical oral status on OIDP.…”
Section: Discussionmentioning
confidence: 98%
“…Population‐based studies have shown that prevalence of oral impacts on the quality of life of older people ranged between 14% and 57.8% worldwide . Other less representative cross‐sectional studies have found prevalence of OIDP ranging between 57.9% and 92.7% .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations